International Human Resource Management Text and Cases - ASWATHAPPA, K AND DASH, SADHNA (New Delhi McGraw Hill Education ( India) Private Limited, 2013)
International,Human,Resource,Management,International Human Resource Management
Keywords: International Human Resource Management